Endurance exercise resistance to lipotoxic cardiomyopathy is associated with cardiac NAD+/dSIR2/PGC-1α pathway activation in old Drosophila - Deng-Tai Wen; Lan Zheng; Jin-xiu Li; Dan Cheng; Yang Liu; Kai Lu; Wen-qi Hou (Biology Open, 2019)
Lipotoxic cardiomyopathy is caused by excessive lipid accumulation in myocardial cells and it is a form of cardiac dysfunction. Cardiac PGC-1α overexpression prevents lipotoxic cardiomyopathy induced by a high-fat diet (HFD). The level of NAD+ and Sir2 expression upregulate the transcriptional activity of PGC-1α. Exercise improves cardiac NAD+ level and PGC-1α activity. However, the relationship between exercise, NAD+/dSIR2/PGC-1α pathway and lipotoxic cardiomyopathy remains unknown. In this study, flies were fed a HFD and exercised. The heart dSir2 gene was specifically expressed or knocked down by UAS/hand-Gal4 system. The results showed that either a HFD or dSir2 knockdown remarkably increased cardiac TG level and dFAS expression, reduced heart fractional shortening and diastolic diameter, increased arrhythmia index, and decreased heart NAD+ level, dSIR2 protein, dSir2 and PGC-1α expression levels. Contrarily, either exercise or dSir2 overexpression remarkably reduced heart TG level, dFAS expression and arrhythmia index, and notably increased heart fractional shortening, diastolic diameter, NAD+ level, dSIR2 level, and heart dSir2 and PGC-1α expression. Therefore, we declared that exercise training could improve lipotoxic cardiomyopathy induced by a HFD or cardiac dSir2 knockdown in old Drosophila. The NAD+/dSIR2/PGC-1α pathway activation was an important molecular mechanism of exercise resistance against lipotoxic cardiomyopathy.